Eco-engineering applications for erosion and sediment control under tropical conditions - Roslan Hashim (Institute of Ocean and Earth Sciences monograph series, 2008)
This book looks into the construction management practices and technical measures implemented in the control of erosion and sedimentation problems in Malaysia. The roles played by project developers, consultants, contractors, local authorities and regulatory agencies are highlighted as effectiveness relies on the participation and cooperation from these parties. This book reviews current practices in relation to erosion and sedimentation problems associated with the various phases of construction project implementation. It also reviews the use of eco-engineering applications to improve construction practices and to minimize problems. Various case studies are highlighted, for example works at Shah Alam II, Putrajaya, Seremban-Kuala Klawang Road, and Puchong where Best Management Practices have been adopted by contractors and enforced or monitored by authorities and developers. This book will be of interest to academician, engineers, ecologists, contractors, project developers, local authorities and post-graduate students.